a. 4^(-3) = 1/(4^3) = 1/64 = -64
b. -2^(-2)*(2^(8)) = -(1/4)*(256) = -64
c. (2^(8)-2^(4))/(2^(2)) = (256-16)/4 = 240/4 = 60
d. -((1)/(4))^(-3) = -4^3 = -64
e. 2^(3)*2^(2)*2^(0) = 8*4*1 = 32
The expressions that are equivalent to -64 are:
a. 4^(-3)
b. -2^(-2)*(2^(8))
d. -((1)/(4))^(-3)
which expressions are equivalent to -64? check all that apply
a. 4^(-3)
b. -2^(-2)*(2^(8))
c. (2^(8)-2^(4))/(2^(2))
d. -((1)/(4))^(-3)
e. 2^(3)*2^(2)*2^(0)
3 answers
only 2 answers
The expressions that are equivalent to -64 are b. -2^(-2)*(2^(8)) and d. -((1)/(4))^(-3).